Penentuan Keabsahan Dokumen KHS Dengan Menggunakan QR Code dan Digital Signature di Politeknik Negeri Manado - Lordan Kimbal, Heaven; Sudarsono, Amang; Winarmo, Idris (The Indonesian Journal of Computer Science, 2024)
The change in the KHS process from manual to computerized has positive impacts such as integration with the judicial system, ease of inputting and printing data, and in recapitulating data. However, there are risks in this concept, namely loss and damage to data which can cause doubts about the validity of KHS data. Departing from this problem, an idea emerged to create a system that can prove the validity of KHS printed documents by applying QR Code technology and Digital Signature. With Digital Signature, information about the contents of KHS when it is first printed is encrypted first so that it cannot be changed by unauthorized parties, then the encryption results will be stored on the QR Code. So that the determination of document validity is done by comparing the contents of the current document with the contents of the document in the QR Code, if the information from both is the same then the printed document is declared an original document and vice versa. The verification process will use hash logic which is one of the functions of providing verification and authentication because it produces a unique value for each input. This result is expected to help Politeknik Negeri Manado to check the validity of KHS printed by students.